THE PHENOMENON OF CODE-SWITCHING AND ITS ROLE IN LINGUISTIC EVOLUTION - Buriyeva , Mukhayyo (Zamonaviy filologiya muammolari, 2025)
Code-switching is a crucial mechanism driving linguistic evolution in multilingual communities. It profoundly influences vocabulary (through borrowing and hybrid words), grammatical structures (by combining syntactic patterns), cultural identity, and social interaction. As a performative and strategic communicative tool, it allows speakers to express group affiliation, navigate social dynamics, and enhance understanding. The sustained practice of code-switching acts as a dynamic force, formalizing innovative constructions and reflecting complex social and cultural change.